Nghiên cứu vai trò của các tương tác trong việc làm bền các phức giữa CO2 với C2H3X (X = H, F, Cl, Br) - Trung, Nguyễn Tiến; Khánh, Phạm Ngọc; Thanh Phương, Ngô Thị; Tuấn, Nguyễn Lê; Nhật, Phạm Vũ; Huế, Trần Thành; Thu Trang, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
The interactions of ethylene and its monohalogen–substituted derivatives with CO2 were investigated. Interaction energies of 16 stable complexes obtained range from -1.13 to -5.57 kJ.mol-1 at the CCSD(T)/aug-cc-pVDZ//MP2/aug-cc-pVDZ level. The stability of the C2H4∙∙∙ CO2 complex is determined by the π∙∙∙π interaction which is due to electron density transfer from MO-π(C=C) to MO‑π*(C=O) dominating the transition from MO-π(C=O) to MO-π*(C=C). Remarkably, contribution of the π∙∙∙π interaction to strength of complex of CO2-philic compounds and CO2 has been revealed for the first time. Substitution of an H atom by a halogen in C2H4 makes CO2∙∙∙C2H3X (X = F, Cl, Br) slightly more stable than CO2∙∙∙C2H4, and all the halogenated derivatives have equivalent stability. The strength of CO2∙∙∙C2H3X which is contributed by Lewis acid-base interaction, attractive electrostatic interaction and hydrogen bond, is different from the case of CO2∙∙∙C2H4. The obtained results also show that, upon complexation, a contraction of C-H bond length involved in hydrogen bond and an increase in its stretching frequency are affected by shape of the complex beside predominant dependence on polarity of C-H bond in isolated monomer.